Reconstruction of Criminal Limits For The Spread of Terrorist Propaganda on Social Media - Amdex Dwi Setyo Yudho; Tahegga Primananda Alfath (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze the limitations of criminal punishment for the dissemination of terrorist propaganda on social media and to formulate a more proportional reconstruction of criminal law policy. The approach used is normative legal research with descriptive-analytical specifications through a literature study of relevant legislation, court decisions, and scientific literature. The analysis was conducted qualitatively using grammatical, systematic, and teleological interpretation methods to assess the suitability of positive legal norms with the development of digital propaganda modes. The results show that the current legal formulation still leaves ambiguity in distinguishing the level of involvement of propaganda disseminators on social media, thus potentially leading to overcriminalization. The proposed reconstruction emphasizes the importance of differentiating criminal liability based on intent, links to terrorist networks, and the potential real impact of content dissemination. This model is expected to achieve a balance between effective counterterrorism and the protection of human rights in a democratic state governed by the rule of law.